2007
DOI: 10.1089/thy.2006.0142
|View full text |Cite
|
Sign up to set email alerts
|

High Energy Shock Waves Activate 5′-Aminolevulinic Acid and Increase Permeability to Paclitaxel: Antitumor Effects of a New Combined Treatment on Anaplastic Thyroid Cancer Cells

Abstract: These preliminary data suggest the possibility of using HESW and ALA in combination with paclitaxel as a promising new therapy in the treatment of anaplastic thyroid cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Indeed, we here demonstrated that NB entrance was significantly increased by ESW treatment. Accordingly, it has already been reported that ESWs increase cell permeability [15,16,18], affecting drug efficacy in breast cancer cells [14], in anaplastic thyroid cancer cells [18], and in an in vivo breast cancer model [19]. Therefore, NBs can act as stable taxane reservoir in the castration-resistant prostate cancer cells and ESWs further increase drug release from NBs, leading to higher cytotoxic and anti-migration effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we here demonstrated that NB entrance was significantly increased by ESW treatment. Accordingly, it has already been reported that ESWs increase cell permeability [15,16,18], affecting drug efficacy in breast cancer cells [14], in anaplastic thyroid cancer cells [18], and in an in vivo breast cancer model [19]. Therefore, NBs can act as stable taxane reservoir in the castration-resistant prostate cancer cells and ESWs further increase drug release from NBs, leading to higher cytotoxic and anti-migration effects.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported elsewhere [17], that ESWs enhance cytotoxicity of doxorubicin-loaded glycol chitosan NBs in anaplastic thyroid cancer cells. Moreover, ESWs increase paclitaxel-induced apoptosis in breast cancer cell lines [14], in anaplastic thyroid cancer cells [18] and in a Mat B-III rat syngeneic model of breast cancer [19]. Lastly, they enhance the cytotoxic effect of doxorubicin and methotrexate in human osteosarcoma cell lines [20].…”
Section: Introductionmentioning
confidence: 99%
“…Extracorporeal shock waves (ESWs) are short-duration focused acoustic waves widely used in urology for lithotripsy (Rassweiler et al 2011) and, more recently, in several musculoskeletal diseases (Wang 2012). ESWs can be focused with high precision in depth, and they determine permeabilization of plasma membranes (Lauer et al 1997, Kodama et al 2002, Frairia et al 2003, Catalano et al 2007. As a consequence of ESWinduced cell permeability, ESWs increase the cytotoxic effects of different anti-cancer drugs (Frairia et al 2003, Palmero et al 2006, Catalano et al 2007, Canaparo et al 2008.…”
Section: :6mentioning
confidence: 99%
“…ESWs can be focused with high precision in depth, and they determine permeabilization of plasma membranes (Lauer et al 1997, Kodama et al 2002, Frairia et al 2003, Catalano et al 2007. As a consequence of ESWinduced cell permeability, ESWs increase the cytotoxic effects of different anti-cancer drugs (Frairia et al 2003, Palmero et al 2006, Catalano et al 2007, Canaparo et al 2008. All these features make ESWs an ideal tool to be used in combination with drug-loaded NBs.…”
Section: :6mentioning
confidence: 99%
“…Furthermore, encapsulation in NPs provided other pathways for uptake and intracellular release of the drug. The hydrophobic Paclitaxel in solution is taken up by tumor cells primarily by diffusion through the cell membrane (58,59). On the other side, Paclitaxel loaded NPs attach to tumor cell membrane (although the extent of attachment in the absence of specific ligand-receptor interaction is low), which minimizes the gradient between the extracellular matrix and cell surface, and are internalized by pinocytosis or phagocytosis.…”
Section: Tumor Cell Viabilitymentioning
confidence: 99%